Determination of spatial fidelity required to accurately mimic the flight dynamics of a bat. (24th September 2019) - Windes, Peter; Tafti, Danesh K; Müller, Rolf
Abstract: Bats possess unique flight capabilities enabled by their wing morphology. While the articulated bone structure and flexible membrane constituting the wing are known to play a critical role in aerodynamic performance, the relationship has never been robustly quantified. Characterization of the sensitivity between precise wing contour and aerodynamic performance is important when designing a biomimetic flight vehicle based on experimentally measured wing kinematics. 3D optical motion capture, a standard method for obtaining wing kinematic measurements, discretely samples the smooth surface of a bat wing during flight. If the constellation of tracked 3D points is too sparse, a loss of critical information occurs. Here, we have explored the relationship between the density of wing surface points and several aerodynamic metrics, specifically, wing surface area variation, aerodynamic loads, and power expenditure. Loads and power were calculated using an incompressible Navier–Stokes solver. Of the metrics examined, aerodynamic power was found to be most sensitive to the spatial fidelity of the wing—the normalized root mean squared difference (NRMSD) between the 10- and 238-point cases was 35%. Load calculations varied slightly less with a peak NRMSD of 24% between the highest and lowest fidelity cases. Lastly, the wing surface area was least sensitive to the spatial fidelity of the wing kinematics, with a maximum NRMSD surface area of 8%. Close similarity in aerodynamic behavior was observed when using either a 120- and 238-point surface representation, establishing a bound to the sensitivity between wing shape and aerodynamics. The results from the 10- and 22-point configurations demonstrate that sparse representation of a wing surface can lead to a loss of information. The characterization of kinematic complexity of the wings both informs how many degrees of freedom are important to measure and also informs how many degrees of freedom are required to robotically reproduce the flapping flight.